Design and implementation of unmanned surface vessel long-distance communication system - Xue LI; Haiju HU; Weiping WANG; Yankun CHEN; Bing ZHENG; Chao DONG (Dianxin kexue)
Unmanned surface vessel (USV) long-distance communication has important use in marine survey operations.The design and equipment development of USV long-distance communication system were carried out from both shore-side communication equipment and boat-mounted communication equipment, and the broadband and narrowband tests of the communication system were carried out in Wanshan and Yellow Sea with the assistance of tethered UAV to conduct communication range test for the whole system.The test results show that when the shore-side communication equipment is raised 129 m, the broadband communication can reach 45 km, when the shore-side communication equipment is raised 180 m, the narrowband communication can reach 50 km, and the communication quality is stable and reliable, meeting the long-distance communication needs of USV.